From the University to the Pluriversity? - Sebastián Maya Tapiero; Diana Albarrán González; Angus Donald Campbell (Diseña)
Decolonization initiatives in design have sparked growing interest among academics worldwide. While these initiatives foster collaborative design with diverse communities in Latin America, their theories and practices often diverge significantly. How to critically integrate these decolonial models into learning processes and knowledge creation with other communities within the university? To address these questions, we undertake a reflexive critical literature review from an artisanal perspective, moving away from objective systems and standardized measurements of knowledge, integrating our experiences, and highlighting our concerns as educators and students from the Global South. This review highlights two key themes in decolonial studies literature: understanding power relations and the roles in knowledge production, and identifying prevailing ideas and practices in knowledge creation with other entities. Using this information, we establish a three-way conversation to examine the limits of neoliberal modern-colonial education within reflexive critical practice, drawing on our own experiences and positionalities.